Pharmacological activity and targeted delivery of supramolecular fenbendazole obtained by mechanochemical technology with various components - A. I. Varlamova; I. A. Arkhipov; V. E. Abramov; M. V. Arisov; S. S. Khalikov; A. V. Dushkin (Российский паразитологический журнал, 2021)
The purpose of the research is studying the influence of various components on the targeted delivery of fenbendazole and evaluation of their efficacy in mice experimentally infected with Trichinella spiralis.Materials and methods. The experiment used 80 white mice experimentally infected with T. spiralis, at a dose of 200 larvae per animal. Each group of 10 animals was administered intragastrically solid dispersion of fenbendazole (SDF) with polyvinyl pyrrolidone (PVP), arabinogalactan (AG), disodium salt of glycyrrhizinic acid (Na2 GA), sodium dioctyl sulfosuccinate (SDS), licorice extract (LE) and hydroxyethyl starch (HES) at a single dose of 2.0 mg/kg of active substance as compared with the fenbendazole substance at the same dose. The control group did not receive the drug. The anthelmintic efficacy was studied by the results of necropsy of the small intestine of mice on the second day after drugs administration. The concentration of fenbendazole and its metabolites in the small intestine was determined by high-performance liquid chromatography with tandem mass spectrometry detection.Results and discussion. SDF with PVP, AG, Na2 GA, SDS, LE and HES showed 98.0, 94.9, 96.6, 100, 86.0 and 81.0% efficacy against intestinal nematode T. spiralis at a dose of 2.0 mg/kg of AS (fenbendazole). The maximum concentration of fenbendazole and its metabolites – sulfone and sulfoxide - was determined in the small intestine wall of animals on the second day after SDF with SDS administration and amounted to 3117.8, 614.6 and 2998.6 ng/g respectively. After fenbendazole substance administration, the drug and its metabolites were found in trace quantity.